2021
DOI: 10.3390/diagnostics11081420
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Based Screening Tests Results: HPV, Liquid-Based Cytology, and P16/Ki67 Dual-Staining in Private-Based Opportunistic Cervical Cancer Screening

Abstract: The baseline data from the private-based opportunistic cervical cancer screening with HRHPV14, liquid-based cytology (LBC) and p16/Ki67 testing, and its quality assessment/quality control (QA/QC) tools are lacking. The age-stratified analysis of 30,066 screening tests results in a Polish population, including the investigation of HRHPV14 status, LBC, and p16/Ki67 dual-staining reporting rates, along with immediate histopathologic correlations, was conducted. For cytopathologic QA/QC, the College of American Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…It has been calculated that adding a cytological sample to hrHPV screening would lead to an earlier detection of, at most, five cases per million women in a year [ 12 ]. Adding a p16/Ki67 dual-stain to screening has been reported to increase the detection rate of histological HSIL among hrHPV positive and cytology negative cases [ 35 ]. A positive Hepika test on a cytological sample seems to have a high sensitivity for invasive carcinoma, both squamous and glandular, in comparison to precursor lesions [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been calculated that adding a cytological sample to hrHPV screening would lead to an earlier detection of, at most, five cases per million women in a year [ 12 ]. Adding a p16/Ki67 dual-stain to screening has been reported to increase the detection rate of histological HSIL among hrHPV positive and cytology negative cases [ 35 ]. A positive Hepika test on a cytological sample seems to have a high sensitivity for invasive carcinoma, both squamous and glandular, in comparison to precursor lesions [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liquid-based cytology has gradually replaced the traditional Pap smear in specimen collection and specimen preparation technology, and according to some studies, the positive detection rate of liquid-based cytology in squamous epithelial lesions and cervical cancer can reach 93% and 100%, respectively. However, the positive detection rates of traditional Pap smears in the above two cervical lesions are 77.80% and 90.90%, respectively [ 11 , 12 ]. The results of this study showed that the positive rate of liquid-based cytology test results increased with the increase of pathological grade.…”
Section: Related Workmentioning
confidence: 99%
“…The sensitivity of p16/Ki67 immunotesting triage higher than almost 20% compared to cytology as in our investigation (92.3%–95.7% vs. 74.4%–84.8% for CIN2+; 90.9%–100.0% vs. 81.8%–87.5% for CIN3+) were also noted by Wright et al 20 and by Giorgi Rossi et al 12 Our study results revealed a relatively low specifitity of triage with cytology (14.3%–16.8% for CIN2+; 16.5%–17% for CIN3+) compared with levels reported, 44.6% for CIN2+ and 42.9% for CIN3+ by Wentzensen et al, 30 76.6% for CIN2+ by Giorgi Rossi et al, 12 or 75.0% for CIN3+ reported by Wright et al 20 It must be noted that the specificity may have been understimated since the proportion of true negative cytology results in HPV‐positive women with NILM cytology was relatively small due to limited indications for colposcopy in that group (especially for N16/N18‐positive cases) and concurrently large number of false positive cytology rates in our population. Whilst it should be rememebered a good quality of a gynecological cytopathology in the study 24 …”
Section: Discussionmentioning
confidence: 99%
“…Whilst it should be rememebered a good quality of a gynecological cytopathology in the study. 24 Our analysis is one of the few large studies evaluating p16/Ki67 diagnostic performance as a triage in HRHPV-positive patients in primary HPV screening setting with limited genotyping for HPV16/ 24.7% vs. 9.0% for HSIL/CIN3+, respectively), regardless of the cut-off point. Similar differences in PPV levels between HRHPVpositivity in p16/Ki67 triage have been reported by others for CIN2+ and CIN3+.…”
Section: Combining Primary Hpv With Limited Genotyping With P16/ki67 ...mentioning
confidence: 96%